The consumer preferences for processed meat products based on choice brand priorities - Muzayyanah, M. A. U. (2022)
Processed animal protein is typically preferred over fresh livestock products for consumption because it is more stable and environmentally friendly when stored over a long period. Therefore, this preliminary study aimed to determine consumer preferences for processed meat products based on consumer choice brand priorities. The consumers were asked to select three preferred processed meat product brands, including sausage, corned beef, meatballs, nuggets, and meat floss, as well as the primary reason for their selection. The study included 450 meat consumers who were selected by purposive sampling. Subsequently, descriptive statistics and Chi-Square analysis were used to determine the preferences among the three product selections. The results showed that the three main preferences of consumers in selecting processed meat products were based on taste, quality, and price in that order. Consumers preferred and selected products with superior taste and quality but were more likely to consider price as the priority decreased. Therefore, the ability to understand consumer preferences plays a key role in developing a sustainable product since cost is not considered a primary concern. © Published under licence by IOP Publishing Ltd.